2023
DOI: 10.3390/biomedicines11030722
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-Mediated mRNA Decay Factor Functions in Human Health and Disease

Abstract: Nonsense-mediated mRNA decay (NMD) is a cellular surveillance mechanism that degrades mRNAs with a premature stop codon, avoiding the synthesis of C-terminally truncated proteins. In addition to faulty mRNAs, NMD recognises ~10% of endogenous transcripts in human cells and downregulates their expression. The up-frameshift proteins are core NMD factors and are conserved from yeast to human in structure and function. In mammals, NMD diversified into different pathways that target different mRNAs employing additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 197 publications
(409 reference statements)
0
8
0
Order By: Relevance
“…( C ) Schematic of the Octet Bio-Layer Interferometry (BLI) system, using biotin-streptavidin coated surface sensors (1). Sensors were sequentially dipped into wells with 10 nM of 50 nt biotinylated DNA oligonucleotide (2), buffer (3), varying concentrations of UPF1-CH-HD (4), buffer (5), and 2 mM ATP and 50 µM of 51 nt trap strand (not shown for clarity) (6). ( D-E ) Representative BLI traces of UPF1-CH-HD WT ( D ) and I757R ( E ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( C ) Schematic of the Octet Bio-Layer Interferometry (BLI) system, using biotin-streptavidin coated surface sensors (1). Sensors were sequentially dipped into wells with 10 nM of 50 nt biotinylated DNA oligonucleotide (2), buffer (3), varying concentrations of UPF1-CH-HD (4), buffer (5), and 2 mM ATP and 50 µM of 51 nt trap strand (not shown for clarity) (6). ( D-E ) Representative BLI traces of UPF1-CH-HD WT ( D ) and I757R ( E ).…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotide sequences are provided in Supplementary Table S1. 4 105 and is also made available for use under a CC0 license.…”
Section: In Vitro Transcription and Substrate Annealing For Biochemic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which Upf1 mediates mRNA decay depends on the interacting proteins available, which is determined by the cells’ proliferative and differentiation state ( Z. Sun et al, 2011 ; L. Sun et al, 2023 ). Our data indicate that Upf1–SMG7 interaction is present in PTC-containing mutants but that the interaction is not required for physiological app family expression regulation.…”
Section: Discussionmentioning
confidence: 99%
“…During the process, a number of frameshift mutations may avert from NMD, and probably induce immune reactions [11]. Many previous studies also have indicated that abnormal transcripts which evade from NMD may encode neoantigens potentially triggering immune responses in cancer patients [12][13][14].…”
Section: Introductionmentioning
confidence: 99%